Правители России. XX век - Данцев Андрей Андреевич (Серия "Исторические Силуэты", 2000)
Экземпляры: ф.9 (20210622) / Инвентарный номер: 45895 / Цена: / Сис.шифр: 63.3(2)6 / Авт.знак: Д 19 / ББК: 63.3(2)6